A política de inovação e sua aplicação na Universidade Federal do Amazonas - Oliveira, Lúcia Martins Pereira de (Brasil, 2021)
The purpose of this article is to verify the main actions that the Federal University of Amazonas has been developing to comply with the provisions of its Innovation Policy, as the resources are being applied in the technological research and the results with potential in Intellectual Property, visualizing the evolution of the deposits and records from 2014 to 2018. We analyzed the University Management Reports of this period and complementary sources. The applied methodology was the qualitative and quantitative, as well as documental and bibliographical research, where we tried to analyze the data of the Reports and confront them with the Innovation Policy. It has been found that the University is committed to complying with its Innovation Policy guidelines, managing the resources it receives for technological research and promoting the protection of its intangible asset.